Case Report: Dangerous liaisons between splenectomy and eltrombopag-induced chronic thromboembolic pulmonary hypertension in patients with immune thrombocytopenia: report of two cases and review of the literature - Roberto Castelli; Enrico Atzori; Alessandro Palmerio Delitala; Salvatore Antonio Masala; Valentina Micheluzzi; Enrico Ponti; Enrico Ponti; Giuseppe Sanna; Dante Castro; Antonio Gidaro; Mattia Donadoni; Roberto Manetti; et al. (Frontiers in Cardiovascular Medicine)
IntroductionPrimary immune thrombocytopenia is an autoimmune bleeding disorder characterized by variable immune-mediated platelet destruction. These patients have reported thrombotic complications, both venous and arterial, in addition to bleeding. Splenectomy and thrombopoietin receptor agonists are recommended for patients who do not respond to steroids or immunosuppressive treatments. Chronic thromboembolic pulmonary hypertension is a rare disease that results from a persistent, organized thromboembolic obstruction of the pulmonary arteries due to an incompletely resolved pulmonary embolism.Case presentationsWe report two cases of chronic thromboembolic pulmonary hypertension induced by a thrombotic mechanism after treatment with splenectomy and Eltrombopag, a thrombopoietin receptor agonist, for refractory primary immune thrombocytopenia. Consequently, the patients were referred for surgical pulmonary thromboendarterectomy therapy as suggested.ConclusionIn older patients, those with a history of thrombotic manifestations, or those with high-risk factors, clinicians should evaluate and monitor the risk of thrombotic events and chronic thromboembolic pulmonary hypertension when treating primary immune thrombocytopenia with splenectomy and Eltrombopag.